Implementasi Pasal 9 Ayat (3) Peraturan Bupati Lampung Barat Nomor 30 Tahun 2021 terhadap Karang Taruna Perspektif Siyasah Tanfidziyyah - Dimas Septian Adi Prasetyo (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the implementation of Article 9 Paragraph (3) of West Lampung Regent Regulation Number 30 of 2021 on Karang Taruna in Gedung Surian Village from the perspective of siyasah tanfidziyyah. The main issue identified is the low participation of youth and the inactivity of the Karang Taruna organization, despite the village government providing funds and supporting youth activities. This indicates that the policy has not been fully effective due to weak organizational leadership, limited communication and insufficient youth engagement. If these issues are not addressed, the potential of Karang Taruna as a platform for youth empowerment will be diminished, hindering the development of youth capacities and reducing the effectiveness of village government programs in fostering social and community participation. Supporting factors include budget availability and the commitment of the village government, while inhibiting factors include weak organizational leadership, limited communication and low youth participation.